Dynamical energy analysis on mesh grids: a new tool for describing the vibro-acoustic response of complex mechanical structures - Chappell, David J.; Loechel, Dominik; Sondergaard, Niels; Tanner, Gregor (Elsevier, 2014)
We present a new approach for modelling noise and vibration in complex mechanical structures in the mid-to-high frequency regime. It is based on a dynamical energy analysis (DEA) formulation which extends standard techniques such as statistical energy analysis (SEA) towards non-diffusive wave fields. DEA takes into account the full directionality of the wave field and makes sub-structuring obsolete. It can thus be implemented on mesh grids commonly used, for example, in the finite element method (FEM). The resulting mesh based formulation of DEA can be implemented very efficiently using discrete flow mapping (DFM) as detailed in Chappell et al. (2013) and described here for applications in vibro- acoustics. A mid-to-high frequency vibro-acoustic response can be obtained over the whole modelled structure. Abrupt changes of material parameter at interfaces are described in terms of reflection/transmission matrices obtained by solving the wave equation locally. Two benchmark model systems are considered: a double-hull structure used in the ship- building industry and a cast aluminium shock tower from a Range Rover. We demonstrate that DEA with DFM implementation can handle multi-mode wave propagation effectively, taking into account mode conversion between shear, pressure and bending waves at interfaces, and on curved surfaces.